PEMODELAN GUNA LAHAN PERKOTAAN BERDASARKAN DATA POI UNTUK MENDUKUNG PERENCANAAN PARTISIPATIF - Mayastuti, Tiani; Pramono, Retno Widodo Dwi (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2025)
Urban spatial planning involves the design process of cities, including spatial patterns and land use distribution. Through land use arrangement, the functions assigned to physical spaces determine the intensity of urban development. Urban areas typically host economic, social, or cultural activities. Therefore, land use mapping is commonly carried out through field surveys to supplement information about the activities occurring on land cover. This study proposes a model to identify land use by utilizing data derived from community participation. Using Point of Interest (POI) data, information is obtained regarding the spatial distribution of existing activities. The objective of this research is to develop a model that identifies urban land use based on the POIs representing ongoing activities in urban space. The model is constructed by filtering and counting the number of POIs within each urban block. The results show that the proposed model can effectively map urban land use based on community preferences. Thus, this study offers a new approach to land use modeling to support participatory planning.